Structural effects of metallic chromium on its electrochemical behavior - VELIMIR RADMILOVIC; JOVAN P. POPIC; DRAGUTIN M. DRAZIC; BORE JEGDIC (Journal of the Serbian Chemical Society, 2007)
Chromium dissolution in aqueous sulfuric acid solution of pH 1 was studied electrochemically on chromium electrodes with different crystallographic structures. A slow potentiodynamic method was used for the electrochemical measurements in deaerated solutions (purgedwith nitrogen),while the Cr(III) ions in the solution after the corrosion were determined by atomic absorption spectrometry. Three electrode materials with a very dominant crystallite orientation resembling single crystal structures (i.e., 111 and 110) confirmed by the electron backscattering diffraction (EBSD), were used in the experiments. The (111) structures were somewhat more active electrochemically (both anodic and cathodic) than the (110) structure. However, Cr electrochemically deposited in standard plating bath, assumed from literature data to has also the (111) structure, was more than 4 times active for anodic dissolution and, by the same number, less active for cathodic hydrogen evolution. The concentrations of Cr(III) ions determined in the solution after definite times of corrosion of all the materials showed almost two times larger dissolution rates than observed electrochemically by three different electrochemical methods (Wagner–Traud, Stern–Geary, electrochemical impedance spectroscopy). This is explained by the simultaneous occurrence of potential independent chemical dissolution of Cr, by a direct reaction of metallic Cr with H2O molecules, proposed a long time ago by Kolotyrkin and coworkers.